Paul's Letter to the Romans : A Commentary - Hultgren, Arland J (Grand Rapids, Mich. : William B. Eerdmans Pub., 2011)
Building on his own translation from the Greek, Hultgren walks readers through Romans verse by verse, illuminating the text with helpful comments, probing into major puzzles, and highlighting the letter's most inspiring features. He also demonstrates the forward-looking, missional character of Paul's epistle -- written, as Hultgren suggests, to introduce Roman Christians to the major themes of Paul's theology and to inspire in them both confidence in the soundness of his teaching and support for his planned missionary efforts in Spain
Introduction -- Opening,1:1-17 -- The revelation of the wrath of God, 1:18-3:20 -- The revelation of the righteousness of God, 3:21-4:25 -- The new life in Christ, Romans 5:1-8:39 -- Israel in God's plan, 9:1-11:36 -- Serving God and loving others, 12:1-21 -- On governing authorities, love, and conduct, 13:1-14 -- The weak and the strong, 14:1-15:13 -- Paul's plans, 15:14-33 -- Greetings and closure, 16:1-27 -- Appendix 1: The "righteousness of God" in Paul -- Appendix 2: Romans 1:26-27 and homosexuality -- Appendix 3: Pistis Christou : faith in or of Christ? -- Appendix 4: the imagery of Romans 3:25 -- Appendix 5: The text of Romans 5:1 -- Appendix 6: The identity of the "I" in Romans 7 -- Appendix 7: The church as the body of Christ in the letters of Paul -- Appendix 8: House churches and communities in Rome
Includes bibliographical references and indexes
Keywords: Bible. -- Commentaries; Book of Romans - Commentary; Paul's Theology - Romans; Paul's Letter to the Romans - Exegetical Commentary